Lower bounds for the module of determinants of block diagonally matrices - Zarnan, Jumah; Petkov, Milko (Ann. Sofia Univ. Fac. Math. and Inf., 1994)
In the present paper a lower bounds for the block matrices with strongly dominant diagonal and one-sided dominant diagonal have been obtained.